Resistin, a Novel Host Defense Peptide of Innate Immunity - Li, Yanran; Yang, Qiyuan; Cai, Dongjie; Guo, Hongrui; Fang, Jing; Cui, Hengmin; Gou, Liping; Deng, Junliang; Wang, Zhisheng; Zuo, Zhicai (Frontiers in Immunology, 2021)
Resistin, a cysteine-rich protein, expressed in adipocytes, was initially proposed as a link between obesity and diabetes in mice. In humans, resistin is considered to be a pro-inflammatory molecule expressed in immune cells, which plays a regulatory role in many chronic inflammatory diseases, metabolic diseases, infectious diseases, and cancers. However, increasing evidence shows that resistin functions as a host defense peptide of innate immunity, in terms of its wide-spectrum anti-microbial activity, modulation of immunity, and limitation of microbial product-induced inflammation. To date, the understanding of resistin participating in host defense mechanism is still limited. The review aims to summarize current knowledge about the biological properties, functions, and related mechanisms of resistin in host defense, which provides a new insight into the pleiotropic biological function of resistin and yields promising strategies for developing new antimicrobial therapeutic agents.